IMPLEMENTASI PENDEKATAN ETNOSAINS DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMA KELAS XI PADA MATERI FLUIDA STATIS - Fatika, Dina; Zulirfan, Z; Nor, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study to determine the effect of implementing an ethnoscience approach in physics learning on improving the cognitive learning outcomes of eleventh-grade senior high school students on the topic of static fluids. The research was motivated by the need to enhance students understanding of physics concepts through contextual learning that integrates local knowledge and cultural practices with scientific concepts. This study employed a quasi-experimental method using a nonequivalent control group design involving an experimental class that received instruction through the ethnoscience approach and a control class that received conventional instruction. Date were collected through posttest instruments and analyzed using descriptive and inferential statistical techniques. The finding revealed that students taught using the ethnoscience approach achieved significantly higher cognitive learning outcomes than those taught through conventional methods. The integration of local wisdom into physics learning anabled students to relate static fluid concepts to real-life experiences, making learning more meaningful, engaging, and effective. Therefore, the ethnoscience approach can be considered an effective alternative for improving students cognitive learning outcomes in physics, particulary on the topic of static fluids.